An existence result for Hadamard type two dimensional fractional functional integral equations via measure of noncompactness. (June 2021) - Deep, Amar; Deepmala,; Hazarika, Bipan
Abstract: In this article, we investigate the existence of solutions for Hadamard type two dimensional fractional functional integral equations on [ 1, b ] × [ 1, c ] . We use the concept of measure of non-compactness and Darbo's fixed point theorem as the main tool to prove our results. Also, with the help of an example, we discuss the validity of our result.